Effect of virtual group EcoMeditation on psychological conditions and flow states - Church, Dawson; Stapleton, Peta; Gosatti, Donna; O’Keefe, Tom (Frontiers in Psychology, 2022)
Background: A plethora of literature has delineated the therapeutic benefits of meditation practice on psychological functioning. A novel meditative practice, EcoMeditation, includes elements of four evidence-based techniques: The Quick Coherence Technique for regulating heart rate variability (HRV), Emotional Freedom Techniques (EFT), mindfulness, and neurofeedback. Objectives: Changes in psychological symptoms, including anxiety, depression, posttraumatic stress, pain, and happiness were measured following a one-day virtual EcoMeditation training workshop. The current study extended on previous literature by adding measures of transcendent experiences and flow states. Methods. Participants were drawn from a convenience sample of 151 participants (130 female, 21 male) aged between 26 to 71 years (M = 45.1, SD = 9.19) attending a one-day virtual EcoMeditation workshop. They were assessed pre-workshop, post-workshop, and at 3-months follow-up. Results: Post-workshop results (N = 111) indicated a significant reduction in anxiety (-42.3%, p < .001), depression (-37.5%, p < .001), posttraumatic stress (-13.0%, p < .001), and pain (-63.2%, p < .001) Likert mean scores when compared to pre-workshop. There was also a significant increase in happiness (+111.1%, p < .001), flow states (+17.4%, p < .001), and transcendent experiences (+18.5%, p < .001). At 3-months follow-up, a one-way repeated measures ANOVA (N = 72) found significant decreases in anxiety, depression, and pain symptoms between pre-test and post-test, as well between pre-test and follow-up. Flow, happiness, and transcendent experiences increased significantly between pre-test and post-test, as well as between pre-test and follow-up, with over 71% of participants experiencing clinically significant improvements. Significant reductions in posttraumatic stress and depression symptoms between pretest and follow-up were also noted. Conclusion: EcoMeditation is associated with significant improvements in psychological conditions such as anxiety, depression, pain, and posttraumatic stress. EcoMeditation was also shown to enhance flow states and transcendent experiences. The benefits identified were similar to those found in the existing literature and provide support for the use of EcoMeditation as an effective stress reduction method that improves psychological symptoms and enhances transcendent states. Keywords: meditation, anxiety, depression, PTSD, group therapy, virtual, EcoMeditation, Emotional Freedom Techniques (EFT).